Node-Gosper Curve-Based Unknown Sensor Localization Using Single Mobile Anchor in Wireless Sensor Networks - Chi-Chang Chen; Sheng-Bo Wang (International Journal of Distributed Sensor Networks)
The node-Gosper curve is a fractal space-filling curve constructed by recursively replacing each node by a seven-segment generator curve. Here, we propose a novel scheme for describing the path of a node-Gosper curve; the scheme can be used to calculate the coordinates of each turning point of the curve efficiently. The node-Gosper curve serves as a routing path for a single mobile anchor to help unknown sensors locate themselves in the wireless sensor network. In our proposed localization method, the mobile anchor travels along the node-Gosper curve, which covers the entire sensing field, and when it reaches the turning points of the node-Gosper curve, it broadcasts its current location to unknown sensors within a preset communication range. Each unknown sensor estimates its location when it receives at least three messages from the mobile anchor from different locations. Experimental results show that the proposed method outperforms several well-known mobile anchor localization methods in terms of localization accuracy and energy consumption.